The Influence of Macro Economic Factors on Mortgage Market Growth in Kenya - Mogaka, Ariemba J.; Kiweu, Joséphat M.; Kamau, Riro G. (Science Publishing Group, 2015)
This study examines the influence of macro-economic variables on the growth of the mortgage market in Kenya. Panel data is collected for a 30 year period, from 1984 to 2013 on the outstanding Real Estate Loan Portfolio as the dependent variable and the macro-economic variables of Average Yearly Inflation Rate, Average Yearly GDP growth Rate, Average Yearly Exchange Rate, Percentage Informal Sector Employment, Treasury bill rate and National Savings Rate as the predictor variables. Regression Analysis was used and the study found no evidence of significant influence of inflation, average GDP growth rate, Treasury bill rate and national savings rate on total real estate loan portfolio. However, the study finds evidence of relationship between informal sector employment, the per capita income and exchange rate. However, the model showed that 81% of the variation in the dependent variable could be explained by the predictor variables.
Keywords: Real Estate; Mortgage Market; Macro-Economic Factors